2019
DOI: 10.3390/medicina55090538
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Analysis in Obstructive Sleep Apnea Syndrome: A Review of the Literature

Abstract: Background and Objectives: Obstructive sleep apnea syndrome (OSAS) represents an independent risk factor for cardiovascular, metabolic and neurological events. Polysomnography is the gold-standard for the diagnosis, however is expensive and time-consuming and not suitable for widespread use. Breath analysis is an innovative, non-invasive technique, able to provide clinically relevant information about OSAS. This systematic review was aimed to outline available evidence on the role of exhaled breath analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Previous studies have reported that F ENO levels in patients with OSA and inflammatory metabolites were increased compared with those of healthy subjects. 20 , 21 Our study also showed that markers, such as age, male sex, BMI, the narrowest transverse diameter of the upper airway, normal tonsil size, and the level of F ENO , were positively related to the severity of OSA. Elevated F ENO levels in patients with OSA indicate the presence of inflammation in the bronchial and upper airway.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have reported that F ENO levels in patients with OSA and inflammatory metabolites were increased compared with those of healthy subjects. 20 , 21 Our study also showed that markers, such as age, male sex, BMI, the narrowest transverse diameter of the upper airway, normal tonsil size, and the level of F ENO , were positively related to the severity of OSA. Elevated F ENO levels in patients with OSA indicate the presence of inflammation in the bronchial and upper airway.…”
Section: Discussionsupporting
confidence: 62%
“…Studies show enhanced levels of inflammatory markers related to oxidative stress in the exhaled breath of OSA patients. Markers of chronic inflammation were enhanced, showing an increase in pro-inflammatory cytokines, while anti-inflammatory cytokines decreased [47]. Furthermore, elevations of toxic volatile organic compounds in patients with OSA were observed [38].…”
Section: Obstructive Sleep Apneamentioning
confidence: 96%
“…Therefore, monitoring isoprene levels in exhaled breath under normal conditions may provide a non-invasive method to detect, monitor, and control disorders of sleep. In the literature, there are very few studies on the development of sensors for the diagnosis of OSAS (Carpagnano 2011, Bikov et al 2016, Finamore et al 2019, Gouma et al 2011, Gouma 2018. There has been increasing interest in the investigation of lungs by non-invasive means measuring the exhaled breath volatile mediators, such as nitric oxide (NO), carbon monoxide (CO), ethane and pentane and finally the non-volatile substances in the liquid phase of exhalate, termed breath condensate.…”
Section: Introductionmentioning
confidence: 99%
“…Bikov et al summarized the results of studies on exhaled breath condensate biomarkers, exhaled volatile compounds and exhaled monoxides in OSA, and critically reviewed methodological limitations (Bikov et al 2016). Furthermore, Finamore et al reported that exhaled breath analysis has demonstrated a clinical relevance in identifying individuals affected by the disease, in assessing the response to treatment and, potentially, to monitor patient's adherence to mechanical ventilation (Finamore et al 2019). After these inspiring studies, Gouma et al described a new concept of a microsystem with three-nanosensor array which potentially serving as a coarse diagnostic tool handheld breath analyzer to provide a first detection device.…”
Section: Introductionmentioning
confidence: 99%